Pemerolehan fonem frikatif kanak-kanak prasekolah dialek Kelantan di Daerah Kota Bharu - Amin, Adi Syafiq Che Mohd (Universiti Sains Malaysia, 2012)
This study aimed to examine ‘Kelantan dialect preschool children acquisition of fricative phonemes in the district of Kota Bharu’ for normal children 4, 5 and 6 years old in selected kindergartens in Kubang Kerian, Kelantan. This data is important to examine the acquisition of fricative phonemes and phonological process that occurs in the speech of preschool children that uses the Kelantan dialect in the district of Kota Bharu, Kelantan. The study used pictured stimulus that consisted of 25 pictures and was adapted from a previous study done by Abd Wahid W.Z (2002). A set of test images for naming was used to obtain 5 fricative consonants in the Kelantan dialect for initial, medial and final position in words. Participants needed to name familiar and culturally appropriate picture stimulus. A total of 30 subjects participated in this study which involved 10 children for each age group. Each utterance of the subjects was recorded and transcribed using the International Phonetic Alphabet (IPA). Results showed that preschool children that uses Kelantan Dialect in the district of Kota Bharu has acquired fricative phonemes such as /s/, /r/, /v/, /f/, and /z/ at the initial, medial and final positions of words except for phonemes /v/, /f/, and /z/ which are not in the words of the Kelantan dialect. Exclusively, the fricative phoneme /r/ at the final position of words is not pronounced. Therefore, this finding is parallel with the pronunciation for words in the standard Malay Language. Standard Malay Language speakers also drop the phoneme /r/ at the final position.